2002
DOI: 10.1002/esp.415
|View full text |Cite
|
Sign up to set email alerts
|

Organic litter: dominance over stones as a source of interrill flow roughness on low‐gradient desert slopes at Fowlers Gap, arid western NSW, Australia

Abstract: Thirty-six runoff plot experiments provide data on flow depths, speeds, and Darcy-Weisbach friction coefficients (f) on bare soil surfaces, and surfaces to which were added sufficient extra plant litter or surface stones to provide projected cover of 5, 10 and 20 per cent. Precision flow depth data were derived with a computer-controlled gantry and needle gauge for two different discharges for each plot treatment.Taking a fixed flow intensity (Reynolds number, Re D 150) for purposes of comparison shows means o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
2
8
1
Order By: Relevance
“…According to the results of the present experiment, plant covers of low shrubs, in contrast to the higher plants, provide not only a tight canopy cover but also a dense, permanent litter layer beneath that intercepts rainfall and reduces the erosivity of raindrops (Dadkah and Gifford 1980;Simanton et al, 1991;Geddes and Dunkerley, 1999;Dunkerley et al, 2001;Dunkerley, 2003). Also, once established, plant roots knit the soil and add organic matter to the soil structure, these advantages being absent from bare soil.…”
Section: Runoff and Soil Erosion Productionmentioning
confidence: 78%
“…According to the results of the present experiment, plant covers of low shrubs, in contrast to the higher plants, provide not only a tight canopy cover but also a dense, permanent litter layer beneath that intercepts rainfall and reduces the erosivity of raindrops (Dadkah and Gifford 1980;Simanton et al, 1991;Geddes and Dunkerley, 1999;Dunkerley et al, 2001;Dunkerley, 2003). Also, once established, plant roots knit the soil and add organic matter to the soil structure, these advantages being absent from bare soil.…”
Section: Runoff and Soil Erosion Productionmentioning
confidence: 78%
“…As shown in Figure , the random roughness increased linearly from 1.57 to 2.67 mm with incorporated litter rate ( R 2 = 0.78). Previous studies found that surface roughness affected flow resistance through altering flow pathways and enhancing backwater (Dunkerley, ; Nearing et al, ). The regression analysis found that flow resistance increased linearly ( R 2 = 0.79), whereas flow velocity decreased linearly ( R 2 = 0.78), with soil surface roughness in this study.…”
Section: Resultsmentioning
confidence: 97%
“…The increasing coefficients of determination probably reflected a strengthened relationship between the incorporated litter rate and flow resistance with the slope gradient. The f in this study was less than that of Dunkerley's () experiments under a litter cover treatment, where f ranged from 1.59 to 37.17. This difference was likely caused by the difference in litter treatments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations